Maturity of Digital Transformation in the Shipping Industry: A Case Study Among Enterprises in Gulf Cooperation Council (GCC) Countries - Tif Said Suhail Al Mazroui; Maathir Mohammed Saud Al Alawi; Khafiya Sultan Hamood Al Wahaibi; Bashayar Badar Saif Al Amri; Mohammed Muneerali Thottoli (Department of Naval Architecture - Diponegoro University, 2023)
Digital maturity describes an organization's readiness and ability to change and implement models to remain competitive in the marketplace. Digital transformation (DT) can streamline processes, reduce errors, and increase the speed of operations in the shipping industry, leading to greater efficiency and cost savings. Companies that adopt DT effectively will be better positioned to compete in the rapidly evolving shipping industry. To achieve competitive benefits from the potential of DT, shipping businesses must understand their digital maturity state. The shipping industry lacks a uniform approach to DT, leading to inconsistencies in implementation and measurement. Many shipping companies are hesitant to adopt new technology and processes, leading to slow implementation and limited impact. Hence, the main goal of this case study is to determine the DT maturity of companies in the Gulf Cooperation Council (GCC) countries in shipping. This case study focuses on the maturity of DT in the shipping industry. With an exploratory approach, the aim of the research is to assess the level of DT maturity among shipping companies in the GCC region. This study employs firstly a qualitative, case study methodology and considered items shipping methods, market operating, services provided, technological initiatives, and the company's goals for technological development of three shipping companies, Asyad, Clarion, and Yht Cargo to analyze data. Then a literature review is compiled from 8 papers published between 2020-2023 in international peer-reviewed journals or conference proceedings, obtained through a bibliographic search in the Scopus database. The findings suggest that coercive and mimetic pressures are primarily responsible for digital change. The benefits of DT have been discovered to assist maritime companies use their resources more efficiently, resulting in increased operational efficiency, improved client connections, and increased sustainability.